Peningkatan Kompetensi Guru di Sekolah Menengah Islam Ihsanul Fikri melalui Pelatihan Pengembangan Media Pembelajaran Berbasis Kecerdasan Buatan: Sebuah Studi Mixed-Methods - Rima Dias Ramadhani; Ahmad Ilham; Muhammad Sam’an; Akhmad Fathurohman; Safuan Safuan; Muhammad Munsarif; Lukman Assaffat; Asdani Kindarto; Muhammad Wahyu Anggana; Teguh Firmasyah; M. Amin Syaifani; Afan Arga Ahyana; Adi Nugroho; Janu Yogi Kurnia (Universitas Muhammadiyah Semarang, 2025)
The training program on Artificial Intelligence-based Learning Media Development (P3MP-AI) represents a strategic initiative to enhance the quality of education at the Ihsanul Fikri Integrated Islamic High School. In the rapidly evolving landscape of information technology, the integration of Artificial Intelligence (AI) technology into education has become an urgent necessity. This endeavor aims to address the personalized learning needs, overcome human resource and time constraints, and enhance the overall quality of education in achieving educational goals. Through the Active and Interactive Learning Method (MPB-AI) approach, educators engage in various practical and interactive activities, enabling them to comprehend and applykecerdasan buatanconcepts practically. Evaluation of this training program demonstrates significant achievements in enhancing participants' understanding and skills, as well as a high level of creativity and diversity in AI-based learning media development practices. Thus, this training program has successfully achieved its objectives in improving the quality of education at the Ihsanul Fikri Integrated Islamic High School. Recommendations for future activities include extending the duration of implementation for optimal goal attainment and developing similar activities periodically to continually enhance educators' abilities in delivering more effective and efficient learning experiences.